Patologi Birokrasi Pelayanan Bansos Di Bagian Kesra Kantor Sekretariat Daerah Kabupaten Pekalongan - Dewi Septriana Kumalasari (Universitas 17 Agustus 1945 Semarang, 2024)
The Pekalongan Regency Regional Secretariat Office is a very vital government agency because it has the task of assisting the Regent in formulating policies and administrative coordination for the implementation of regional apparatus duties and administrative services. With this task, SETDA is the